AETIOLOGY, MATERNAL AND FOETAL OUTCOME IN 60 CASES OF OBSTETRICAL ACUTE RENAL FAILURE - Khalil, Muhammad Abdul Mabood; Azhar, Amer; Anwar, Nisar; ullah, Amin; Din, Najm -ud-; Wali, Raj (Journal of Ayub Medical College Abbottabad, 2009)
Background: Acute renal failure is a serious complication in pregnancy. Not only does it result in significant maternal morbidity and mortality but also results in significant number of foetal loss. Although incidence of obstetrical acute renal failure has decreased in developed countries but still it is one of the major health problem of developing nations. The objective of this study was to study aetiology, maternal and foetal outcome in obstetrical acute renal failure. Methods: This study was conducted at Department of Nephrology, Khyber Teaching Hospital, Peshawar from August 2006 to December 2007. It was a descriptive, case series study. Female patients with pregnancy and acute renal failure, irrespective of age, were included in the study. Patients were thoroughly examined and baseline urea, creatinine, serum electrolytes, peripheral smear, prothrombin time, partial thromboplastin time, fibrinogen degradation products, renal and obstetrical ultrasound were performed on each patient and 24-hr urinary protein and bacterial culture sensitivity on blood, urine or vaginal swabs were done in selected patients. Foetal and maternal outcome were recorded. Data were analysed using SPSS. Results: A total of 60 patients were included in the study. Mean age of the patients was 29ï‚±5.4 years and duration of gestation was 33ï‚±4.9 weeks. Mean gravidity was 4ï‚±2.2. Sixteen patients (26.66%) were treated conservatively while 44 (73.33%) required dialysis. Postpartum haemorrhage was present in 14 (23.33%), postpartum haemorrhage and disseminated intravascular coagulation (DIC) in 11 (18.33%), eclampsia-preeclampsia in 8 (13.33%), antepartum haemorrhage in 8 (13.33%), antepartum haemorrhage with DIC in 6 (10%), DIC alone in 4 (6.66%), obstructed labour in 3 (5%), septic abortion in 3 (3.33%), HELLP (haemolysis elevated liver enzyme and low platelet) in 2 (3.33%), urinary tract infection with sepsis in 1 (1.66%) and puerperal sepsis in 1 (1.66%). Foetal loss was 40 (66.66%). Maternal mortality was 9 (15%) while 28 (46.66%) fully recovered. Among the rest 6 (30%) had partial recovery and 5 (8.33%) had dialysis dependent chronic kidney disease. Conclusion: Obstetrical acute renal failure not only results in foetal loss but also causes significant maternal morbidity and mortality. Keywords: Obstetrical acute renal failure, ARF, Aetiology, Foetal outcome, Maternal outcome